Competing perceptions of landscape in the Limi Valley: politics, ecology and pastoralism - Tara Bate (European Bulletin of Himalayan Research)
A common response to the current global ecological crisis is the conservation of areas still somewhat spared from anthropogenic damage, in spite of an abundant literature evidencing the social and ecological shortcomings of top-down approaches to nature conservation. As part of the Kailash Sacred Landscape Initiative, the Limi Valley of north-western Nepal is currently under consideration for the establishment of one such area. This paper warns about an understanding of conservation as a segregation of humans and nature, which is at odds with local perceptions of landscape as relational. Through the perspective of pastoral practices in the Limi Valley, I show how the Limey – the people of this Valley – conceive of humans as enmeshed within a network of interacting beings under the guiding principles of ecological ethics of care. This conception is framed by religion (a syncretic mixture of Mahayana Buddhism, Bön religion and Animism), as well as by skills of ecological and spiritual embeddedness which are central to pastoral practice. I also warn against the fallacy of considering locals’ relationship to the environment, informed by Buddhism, as intrinsically more prone to eco-friendly practices. I show how this relationship is dynamic and evolving, and influenced by the economic and political context of the last thirty years. This has led to the progressive obsolescence of pastoralism as the main means of livelihood, with consequences for the local inhabitants’ relationship to landscape and to other-than-human species.